2013
DOI: 10.1186/1471-2393-13-s1-s10
|View full text |Cite
|
Sign up to set email alerts
|

Key components of early intervention programs for preterm infants and their parents: a systematic review and meta-analysis

Abstract: BackgroundPreterm infants are at greater risk for neurodevelopmental disabilities than full term infants. Interventions supporting parents to improve the quality of the infant’s environment should improve developmental outcomes for preterm infants. Many interventions that involve parents do not measure parental change, nor is it clear which intervention components are associated with improved parental outcomes. The aim of this review was to categorize the key components of early intervention programs and deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
269
1
17

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(291 citation statements)
references
References 70 publications
4
269
1
17
Order By: Relevance
“…17,21 Elevated maternal anxiety is associated with postpartum depression 38 and impaired parenting 39 in mothers of preterm infants, whereas reduction in maternal anxiety is associated with improvements in child development during the first 2 years of life. 40 The 3 studies included in the metaanalysis of maternal anxiety all used live music in conjunction with KC, demonstrating greater improvements than with KC alone. These results support the beneficial impact of interventions that instate the parent in a nurturing and caregiving role (provider of KC) that includes engagement in live music.…”
Section: Figurementioning
confidence: 99%
“…17,21 Elevated maternal anxiety is associated with postpartum depression 38 and impaired parenting 39 in mothers of preterm infants, whereas reduction in maternal anxiety is associated with improvements in child development during the first 2 years of life. 40 The 3 studies included in the metaanalysis of maternal anxiety all used live music in conjunction with KC, demonstrating greater improvements than with KC alone. These results support the beneficial impact of interventions that instate the parent in a nurturing and caregiving role (provider of KC) that includes engagement in live music.…”
Section: Figurementioning
confidence: 99%
“…Apesar de já evidenciada a relevância do envolvimento paterno, ainda se nota a falta de intervenções direcionadas para o aprimoramento específico da atuação do pai junto a seu filho (Benzies, Magil-Evans, Hayden, & Ballantyne, 2013;Flippin & Crais, 2011), bem como a fragilidade metodológica desses programas, quando existentes (Bronte-Tinkew, Burkhauser, & Metz, 2012). Embora recentemente algumas intervenções para pais (homens) já tenham sido criadas, estas, no entanto, não contam com robustos procedimentos de avaliação do envolvimento paterno (Bronte-Tinkew et al, 2007;Lundahl, Tollefson, Risser, & Lovejoy, 2008;McAllister, Burgess, Kato, & Barker, 2012).…”
Section: Avaliação Do Envolvimento Paternounclassified
“…This is unfortunate, as attention to relationships is central to the work that we do with very young children and their families (Achenbach, Howell, Aoki, & Rauh, 1993); Boukydis, 2012;Fitzgerald, Weatherston, & Mann, 2011;Benzies, Magill-Evans, Hayden & Ballantyne 2013;Melnyk, Feinstein, Fairbanks, Schultz-Czarniak, Hust, et. al., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Several key categories of support for parents with babies in the NICU have been identified that are well aligned with I/ECMH practice. These include parent emotional support, parent education, and child development support (Benzies, Magill-Evans, Hayden & Ballantyne, 2013;Purdy, Craig, & Zeanah, 2015). I/ECMH interventions have been shown to result in changes in parent-child interactions, parental mental health status, and child behavior and physiological status in the population of newborn intensive care unit graduates.…”
Section: Nicu and I/ecmhmentioning
confidence: 99%